Impact of Cilostazol Administration on Femoropopliteal In-Stent Restenosis. (October 2017) - Tomoi, Yusuke; Soga, Yoshimitsu; Iida, Osamu; Fujihara, Masahiko; Ando, Kenji
Purpose: To investigate whether administering cilostazol after treatment for femoropopliteal in-stent restenosis (ISR) can have a positive impact on recurrent ISR (Re-ISR).Methods: The database of a multicenter, retrospective, observational registry was interrogated to identify 338 consecutive patients (mean age 72.3±8.8 years; 148 men) who underwent endovascular therapy for femoropopliteal ISR in 379 limbs from January 2010 to December 2014. Ninety-seven patients (103 limbs) who received cilostazol after the initial stent implantation procedure were excluded. This left 24 ISR patients (30 limbs) who received cilostazol initially after ISR treatment for comparison with 217 ISR patients (246 limbs) who did not receive the drug. The primary endpoint was 2-year Re-ISR after treatment. The secondary endpoints were recurrent target lesion revascularization (Re-TLR) and reocclusion at 2 years. Restenosis was determined by a peak systolic velocity ratio >2.4 on a duplex scan or >50% stenosis on angiography.Results: The mean follow-up was 23.3±15.5 months. At 2 years, freedom from Re-ISR was significantly higher in the cilostazol group than in the no cilostazol group (48.6% vs 32.4%, p=0.047). However, freedom from Re-TLR and reocclusion between the 2 groups did not differ significantly [64.7% vs 53.8% (p=0.15) and 88.3% vs 73.9% (p=0.11), respectively]. After adjusting for prespecified risk factors, cilostazol administration was a negative predictor of Re-ISR.Conclusion: This small comparative study suggests that administering cilostazol for ISR lesions after femoropopliteal stenting reduces recurrent ISR.